Modeling and analysis on bipedal wheel-legged robot with sprawling mechanism - Sabilah, Abdul Halim (2022)
Mobile robots have a wide range of applications; they can be used not only in service industries such as manufacturing, agriculture, healthcare, and other specialized fields. As a result, the technology of mobile robots has garnered global attention. Most legged mobile robot use mammal-type mechanism because of the robot can walk at narrow space and can walk faster than sprawling mechanism. However, this type of legged robot has low wide range motion and foot placement is limited as well. Moreover, the stability of the mammal type is lower than sprawling makes this configuration able to locate its center of gravity at low position with wider support polygon. Therefore, this project has proposed a hybrid design and modelled of bipedal robot with combination of mammal and sprawling mechanism. The DH parameters is done in kinematics solution for both forward and inverse kinematics of each leg. Forward kinematics equation is used to measure the output Cartesian position robot from the feedback signal of each joint of each leg. On the other hand, inverse kinematic is used to translate the Cartesian trajectory input to the angular input for each joint of each leg. The multibody dynamic structure of the robot is approached in modeling this robot using MATLAB SIMULINK-Simscape to simulate the motion of the robot and the leg trajectory of the leg motion is designed for robot’s leg working envelope test. The dynamic performance angle are observed from the simulation results for each joint and the input angle is same as an output angle. Moreover, the results of trajectory motion and robot workspace is equality with the desired motion.